Search For A Common Language Environmental Writing And Education - Graulich, Melody; Crumbley, Paul (Utah State University Press, 2005)
A stellar group of writers, scientists, and educators illuminate the intersections between environmental science, creative writing, and education, considering ways to strengthen communication between differing fields with common interests. The contributing authors include Ken Brewer, Dan Flores, Hartmut Grassl, Carolyn Tanner Irish, Ted Kerasote, William Kittredge, Ellen Meloy, Louis Owens, Jennifer Price, Robert Michael Pyle, Kent C. Ryden, Annick Smith, Craig B. Stanford, Susan J. Tweit, and Keith Wilson.